The Importance of Iron in the Body's Metabolic Processes (Global Scientific Review, 2023)
Iron helps to support many important body functions, affecting vitality, concentration, gastrointestinal processes, the immune system and the regulation of body temperature. A shortage or excess of it has an immediate effect on well-being.